Auditory Verbal Hallucinations in Borderline Personality Disorder and the Efficacy of Antipsychotics: A Systematic Review - Slotema, Christina W.; Blom, Jan Dirk; Niemantsverdriet, Marieke B. A.; Sommer, Iris E. C. (Frontiers in Psychiatry, 2018)
Background: Auditory verbal hallucinations (AVH) are experienced more frequently by patients with borderline personality disorder (BPD) than previously assumed. However, consensus is lacking on how to treat them. Objective: To provide a systematic review of studies reporting on AVH in patients with BPD, with a focus on the efficacy of treatment of psychotic symptoms. Methods: For this review a systematic search was made in the PubMed and Ovid databases, and mean weighted prevalence rates, adjusted for sample size, were computed. Results: The search yielded 36 studies describing a total of 1,263 patients. Auditory hallucinations (including AVH) were reported in 27% of hospitalized BPD patients; AVH were reported in 25% of all patients and in 24% of outpatients. Of the hallucinating patients, 78% experienced AVH at least once per day, for a duration of several days to many years. On the whole, patients with BPD regarded their voices as malevolent and omnipotent in nature. Compared to patients with schizophrenia, the phenomenological characteristics of AVH were similar and the ensuing distress was equal or even higher, whereas scores for other positive symptoms were lower. The presence of AVH in BPD was associated with an increase of suicide plans and attempts, and more frequent hospitalization. Moreover, AVH in the context of BPD were associated with higher prevalence rates for post-traumatic stress disorder and emotional abuse. The efficacy of antipsychotics was investigated in 21 studies. Based on these studies, we conclude that both typical and atypical antipsychotics tend to have positive effects on AVH experienced in the context of BPD. The efficacy of cognitive-behavioral therapy and non-invasive brain stimulation has not yet been systematically assessed. Conclusions: These findings indicate that AVH experienced in the context of BPD are in need of proper diagnosis and treatment, and that antipsychotics tend to be beneficial in treating these (and other psychotic) symptoms. There is an urgent need for studies assessing the efficacy of cognitive-behavioral therapy and non-invasive brain stimulation in this underdiagnosed and undertreated group.